Melatonin regulates carbohydrate metabolism and defenses against Pseudomonas syringae pv. tomato DC3000 infection in Arabidopsis thaliana - Zhao, Hongbo; Xu, Lingfei; Su, Tao; Jiang, Yang; Hu, Lingyu; Ma, Fengwang (Journal of pineal research, 2015)
Melatonin has been reported to promote plant growth and development. Our experiments with Arabidopsis thaliana showed that exogenous applications of this molecule mediated invertase inhibitor (C/VIF)-regulated invertase activity and enhanced sucrose metabolism. Hexoses were accumulated in response to elevated activities by cell wall invertase (CWI) and vacuolar invertase (VI). Analyses of sugar metabolism-related genes revealed differential expression during plant development that was modulated by melatonin. In particular, C/VIF1 and C/VIF2 were strongly down-regulated by exogenous feeding. We also found the elevated CWI activity in melatonin-treated Arabidopsis improved the factors (cellulose, xylose, and galactose) for cell wall reinforcement and callose deposition during Pseudomonas syringae pv. tomato DC3000 infection, therefore, partially induced the pathogen resistance. However, CWI did not involve in salicylic acid (SA)-regulated defense pathway. Taken together, this study reveals that melatonin plays an important role in invertase-related carbohydrate metabolism, plant growth, and pathogen defense.